(untitled) (INTERNATIONAL JOURNAL OF RECENTLY SCIENTIFIC RESEARCHER’S THEORY, 2026)
This article investigates the structural and semantic characteristics of measurement units (metrological lexis) in Uzbek and English languages. It examines the linguistic role of measurement units, their anthropocentric nature within the linguistic world view, and their semantic transformations within the phraseological system. The research highlights similarities and contrasts between the metrological systems of both languages, specifically focusing on the issues of maintaining semantic and stylistic identity during the translation of idioms. The results provide practical insights for translation studies, language instruction, and lexical-semantic analysis.